THOUGHTS ON COMMUNICATION IN THE SCIENTIFIC HERITAGE OF EASTERN THINKERS (American Journal of Pedagogical and Educational Research, 2024)
In this article, the ideas of the views on communication in the scientific heritage of eastern thinkers are included. It was studied by them that priority is given to the issues of communication in the development of a person, and a lot of information about the issues of communication was presented.